ASSESSMENT OF INVESTMENT ACTIVITIES OF SMALL BUSINESSES - Karimova Komila Daniyarovna (Scholar Express Journals, 2025)
The article evaluates the system of factors influencing the development of business entities, the trend equation for the share of items in the total number of items in small business entities, the correlation of the interrelated values of the factors of the resulting indicator, the correlation of the logarithmic values of revenue and total assets
Keywords: small business; entrepreneurship